Adjunctive use of tranexamic acid to tourniquet in reducing haemorrhage during abdominal myomectomy - A randomized controlled trial. (November 2019) - Abdul, Ishaq F.; Amadu, Motunrayo B.; Adesina, Kike T.; Olarinoye, Adebunmi O.; Omokanye, Lukman O.
Abstract: Background: Uterine fibroids are the commonest tumour of the female genital tract; about one third are symptomatic and require management. The treatment of uterine fibroids may be medical, surgical, conservative or expectant. Myomectomy is the common surgical treatment option for women failing medical management and desiring to preserve fertility and/or their uterus. The tourniquet is shown to be effective in reducing blood loss during myomectomy and tranexamic to a less extent. However, the adjunctive use of tranexamic acid with tourniquet to further reduce blood loss has not been studied. Aim: The aim of the study was to determine the efficacy of perioperative intravenous tranexamic acid in further reducing blood loss at abdominal myomectomy when used as an adjunct to tourniquet. Methods: The study was a randomized double-blind controlled study involving women who underwent abdominal myomectomy. Participants were randomized to either tourniquet plus intravenous tranexamic acid or tourniquet plus placebo groups using simple random sampling. The primary outcomes were the intra-operative blood loss, post-operative haematocrit values and need for intra-operative blood transfusion. The data was analyzed using the SPSS software version 23.0 and p value < 0.05 was significant. Results: The mean intra-operative blood loss (998.72 ± 607.21 ml vs 907.25 ± 529.85 ml, p = 0.475), intra-operative blood transfusion rate (45% vs. 30%; p = 0.166) and mean unit of blood transfused (1.13 ± 1.64 vs. 0.75 ± 1.28; p = 0.256) were higher for tourniquet plus placebo group compared to tourniquet plus tranexamic acid group. The estimated blood loss per 100 g of fibroid removed was reduced significantly in the tranexamic acid plus tourniquet group (139.80 ± 2.28 ml vs 104.09 ± 1.97 ml; p = 0.001). Strength and limitations: : The strength of the study include randomization and blinding. The limitations included non-uniformity of sizes and locations of fibroids, as well as the different surgeons with possibly different skills, techniques and experiences, though they were statistically not significant. Conclusion: The adjunctive use of tranexamic acid to tourniquet significantly further reduces intraoperative blood loss during abdominal myomectomy when compared to tourniquet alone. Recommendations: Adjunctive use of tranexamic acid is recommended for further reducing intra-operative blood loss during abdominal myomectomy.